Harmonization of Kosovo's legislation with the acquis communautaire in the field of transport : the case of sea ports exploitation - Morina, Fitore (Array, 2019)
The aim of this paper is to present the position of Kosovo from the perspective of exchange, trade and movement of goods and capital, exploiting the benefits of multimodal transport and in particular the exploitation of maritime transport. Initially, this paper addressed the development of multimodal transport in Kosovo by analyzing the legal cooperation of Kosovo with the state and region. The focus of the work is the treatment of multimodal and maritime transport, and the impact on the increase of the level of cooperation besides the economic one in the cultural, educational and tourist aspect. In this paper, comparative, historical, normative and statistical methods have been used to explain the role and importance of the exploitation of the seaports of the countries of the region. Finally, the measures taken to harmonize Kosovo’s legislation with the acquis communautaire in the field of transport have been addressed in this paper.